The time course of the hyperactivity that follows lesions or temporary inactivation of the fimbria-fornix. - Bannerman, D; Gilmour, G; Norman, G; Lemaire, M; Iversen, S; Rawlins, J (2001)
Lesions of the hippocampus or the fimbria-fornix produce a pronounced hyperactivity in rats. This effect is thought to be due to the loss of glutamatergic hippocampal inputs to the nucleus accumbens, although the mechanisms involved remain unclear. It has been suggested that the hyperactivity is due to changes in accumbens dopamine receptors, possibly involving the gradual development of denervation supersensitivity. Consistent with this possibility, the present study found that fimbria-fornix transection produced hyperactivity which, although undetectable immediately after surgery, gradually became apparent and then continued to increase over the course of several days. This does not, however, preclude the possibility that there is an immediate increase in activity which is masked by the after effects of surgery. To address this issue, local anaesthetic was infused into the fimbria-fornix via chronic indwelling cannulae, in order to silence the hippocampal inputs to the nucleus accumbens. This procedure impaired spatial working memory on the elevated T-maze and resulted in immediate hyperactivity, suggesting that there may be at least two components to fornix lesion-induced hyperactivity, and that the immediate effects of mechanical fornix lesions on activity levels may be masked by the after effects of surgery per se.